Effectiveness of the E-Ticket System Using QR Codes For Smart Transportation Systems - Tommy Kuncara; Arman Syah Putra; Nurul Aisyah; VH. Valentino (Publisher Cv. Inara, 2021)
The background of this research is to know the effectiveness of using QR codes for E-ticket payments in the ticket booking system in the transportation sector, by providing easy payments to the public, it will be able to facilitate ordering and payment of tickets, therefore it will be able to increase ticket sales. The research method used is to use the literature review method by reviewing many journals and finding the latest research problems so that the research carried out becomes renewable research and can solve the research problems raised. The problem raised in this study is by analyzing the effectiveness of using QR codes, data obtained from previous research studies, by conducting literature reviews, will be able to find problems and solutions from the research raised. This research will produce a system proposal that will make it easier for the public to use the ticket payment system, the use of QR codes will simplify transactions and speed up the payment process.